Astragalus Polysaccharides Inhibits Tumorigenesis and Lipid Metabolism Through miR-138-5p/SIRT1/SREBP1 Pathway in Prostate Cancer - Guo, Shanqi; Ma, Baojie; Jiang, Xingkang; Li, Xiaojiang; Jia, Yingjie (Frontiers in Pharmacology, 2020)
Astragalus polysaccharides (APS) is a traditional Chinese medicine and have been proved to involve in multiple biological processes, including inflammation, metabolism and carcinogenics. However, the specific mechanisms by which APS on prostate cancer (PCa) remains largely unknown. In the current study, we found APS greatly inhibited the proliferation and invasion of PCa cells in a dose-dependent and time-dependant manner in vitro and in vivo. In addition, cellular triglyceride and cholesterol levels were also decreased significantly under APS treatment. Microarray data revealed the SIRT1 expression was markably suppressed under APS exposure. Mechanistic studies demonstrated that ecoptic expression of SIRT1 inhibits the expression and nuclear translocation of SREBP1 via activating AMPK phosphorylation to suppress lipid metabolism. Otherwise, knockdown of SIRT1 significantly promotes AMPK/SREBP1 signaling and and its associated target genes. Besides, we also found miR-138-5p was greatly inhibited the SIRT1 expression to regulating cell metabolism by targeting its 3’UTR region. To summarize, our findings suggested that APS inhibits tumorigenesis and lipid metabolism through miR-138-5p/SIRT1/SREBP1 pathways in PCa.